Plasmonic mesoporous core-shell Ag-Au@TiO2 photoanodes for efficient light harvesting in dye sensitized solar cells. (15th November 2019) - Salimi, Kouroush; Atilgan, Abdullah; Aydin, Mustafa Yasir; Yildirim, Hilal; Celebi, Nuray; Yildiz, Abdullah
Graphical abstract: Highlights: Mesoporous core-shell Ag-Au@TiO2 NCs were synthesized by seed-mediated growth. Strong metal-dielectric interfacial interaction led to increase charge separation. Superior PCE value ( η = 7.41%) was achieved using Ag-Au@TiO2 NC photoanodes. LSPR properties led to shifting of Fermi level close to the TiO2 conduction band. Low amount of photoanode (0.0125 wt%) was utilized for low-cost device production. Abstract: In this study, plasmonic mesoporous core-shell Ag-Au@TiO2 nanocomposites were synthesized by seed-mediated growth of Ag shell onto Au decorated TiO2 and utilized as photoanodes to enhance the power conversion efficiency (PCE) of dye-sensitized solar cells. The enhanced preserved mesoporous characteristics of photoanodes, together with strong metal-dielectric interfacial interaction between Ag-Au shell, remarkably improved electron transfer ability onto TiO2, which caused to the enhancement of the light harvesting ( η = 7.41% using Ag-Au@TiO2 ) 125% higher than bare TiO2 ( η = 5.91%). These superior PCE value was mainly due to the shifting of the Fermi level close to the TiO2 conduction band thanks to the broad band localized surface plasmon resonance (LSPR) properties between Ag-Au and TiO2 interfaces. The significant outperforming in enhanced solar to electrical energy conversion efficiency using low amount of Ag-Au@TiO2 photoanode (0.0125 wt%) demonstrated a relative low-cost solar device from the economic perspective of renewable energy fabrication resources.